A Measurement Model for River Conservation Behavior Using Confirmatory Factor Analysis (CFA) - Nor Azilawanie Tun Ismail, Wan; Amin, Aziz (International Journal of Engineering and Technology, 2018)
River conservation represents important environmental behavior for a sustainable environment. This research is to measure the validity and reliability of the instrument for measuring river conservation behavior model. The research instrument was administered to 373 respondents who were selected trough cluster sampling in 10 polluted rivers in the Terengganu state, Malaysia. Confirmatory Factor Analysis (CFA) was used to validate the measurement model for items in the behavioral instrument. The findings of the study have dropped 36 items and retained 48 valid and reliable items to measure eleven constructs that affected the residentâ€™s behavior. These behavioral instruments can be used to obtain a community profile as an indicator to improve the behavior of the residents towards river conservation.Â Â